2004
DOI: 10.1103/physreve.70.021202
|View full text |Cite
|
Sign up to set email alerts
|

Stripe patterns in two-dimensional systems with core-corona molecular architecture

Abstract: The behavior of a two-dimensional system of particles interacting through a potential consisting of a hard core surrounded by a soft repulsive corona is investigated at several densities and temperatures. We find that the competition between hard and soft repulsions gives origin to the spontaneous formation of spatial patterns resembling stripe textures. The effect of varying the hard and soft core radii ratio as well as that of adding an attractive component to the interparticle interaction is studied. The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
89
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(97 citation statements)
references
References 39 publications
8
89
0
Order By: Relevance
“…It is possible that the structure of liquid here is 3D analog of the spatial configurations found in Ref. 25. This point clearly requires further study.…”
Section: -5mentioning
confidence: 93%
See 1 more Smart Citation
“…It is possible that the structure of liquid here is 3D analog of the spatial configurations found in Ref. 25. This point clearly requires further study.…”
Section: -5mentioning
confidence: 93%
“…129, 064512 ͑2008͒ potentials. [24][25][26][27] These simulations suggest that such systems have a low-temperature re-entrant liquid phase where particles intend to arrange in more or less complex, locally ordered patterns. Norizoe and Kawakatsu 27 found evidence for local clustering and the formation of percolating clusters in the re-entrant liquid phase of a 3D repulsive-shoulder model.…”
Section: -5mentioning
confidence: 99%
“…To obtain the solution at a given temperature, equations (8) and (9) are solved for fixed λ. Then the free energy is minimized with respect to λ to get the final solution.…”
Section: A Stripes Solutionsmentioning
confidence: 99%
“…Several computational studies on the self-assembly of patchy particles have been reported and these have pushed the imagination of the patchy particle community to new heights. [36][37][38][39][40][41][42] However, the large-scale fabrication of patchy particles is still elusive and requires further research. [16,18,19] This article attempts to present the state-of-the-art in patchy particle fabrication technology and computational efforts for their description, together with a discussion of their potential applications.…”
Section: Introductionmentioning
confidence: 99%